2022
DOI: 10.1038/s41419-022-04963-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the PI3K/AKT signalling pathway in the corneal epithelium: recent updates

Abstract: Phosphatidylinositol 3 kinase (PI3K)/AKT (also called protein kinase B, PKB) signalling regulates various cellular processes, such as apoptosis, cell proliferation, the cell cycle, protein synthesis, glucose metabolism, and telomere activity. Corneal epithelial cells (CECs) are the outermost cells of the cornea; they maintain good optical performance and act as a physical and immune barrier. Various growth factors, including epidermal growth factor receptor (EGFR) ligands, insulin-like growth factor 1 (IGF1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 125 publications
1
21
0
Order By: Relevance
“…Therefore, researchers often use animal diabetes models and in vitro cell models to study pathogenesis (78, 79). The changes in growth factors, immune cells and signal pathways in diabetic keratopathy have been elaborated in previous reviews (4,14,17,78,80). Here, we mainly discuss the following aspects.…”
Section: Pathologic Mechanismsmentioning
confidence: 93%
“…Therefore, researchers often use animal diabetes models and in vitro cell models to study pathogenesis (78, 79). The changes in growth factors, immune cells and signal pathways in diabetic keratopathy have been elaborated in previous reviews (4,14,17,78,80). Here, we mainly discuss the following aspects.…”
Section: Pathologic Mechanismsmentioning
confidence: 93%
“…An imbalance between antioxidant defenses and ROS, produced in large part by mitochondria, induces oxidative stress [ 59 ]. Chen and colleagues in 2022 demonstrated an improvement in the effects of DED reversing hyperosmolarity-mediated mitochondrial dysfunction in HCE-2 [ 60 ]. For this reason, we focused our attention on mtROS levels.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory responses caused by diseases related to the ocular surface can directly damage the epithelial cells of the ocular surface ( 27 ). There is evidence that epithelial apoptosis is closely related to the occurrence of dry eye ( 28 , 29 ), but whether it is involved in the occurrence of GO is unclear. Our results showed that Caspase-3 levels in exosomes from GO patients were higher than those in exosomes from controls, while the levels of Caspase-3 in extraocular muscles in GO patients were significantly higher.…”
Section: Discussionmentioning
confidence: 99%